Design and development of a honey dehydrator - Ma, Amos Rong Sheng (Nanyang Technological University, 2024)
Due to its tendency to yield profits within the first year of operation, beekeeping is a promising avenue for developing impoverished communities. To ensure their honey keeps fresh and doesn’t ferment, beekeepers must ensure that the moisture content of their honey does not exceed a limit. Honey is also heat sensitive and will accumulate unwanted substances such as HMF if heated at high temperatures for long periods of time. For these reasons, temperature-controlled honey dehydration machines are thus crucial pieces of equipment for honey producers. However, the cost of these devices can be prohibitively expensive, especially for small-scale honey producers. Therefore, honey producers often resort to ad-hoc drying methods, whose efficacies are known to vary, most crucially as a factor of environmental humidity. Between these options, a type of small-scale micro-controller-based dehydrator has emerged, which is not as expensive as commercial dehydrators but preferable to most ad-hoc drying methods. This report describes the design and development of a modular microcontroller-base dehydrator with a processing capacity of up to 20kg per run, costing less than SGD 500, with a power usage of less than 1.5kW and a calculated maximum dehydration rate of 25 g/hr. During development, various novel methods to improve the processing capacity of the device were tried, and the results are discussed in this report. Multiple aspects of the design of the dehydrator are also discussed